(A study of The Extraction of Curcuminoid From Turmeric With Water) - Ei Purwanti; S Imamkhasani; Tahid -; Afrizal - (Balai Besar Industri Agro, 1988)
Curcuminoid had been extracted from turmenic roots using six kinds of carboxylic acid with pH range 4,3-4,6 through protein precipitation which has significant role in the floculation process. The efficiency of extraction was evaluated using TLC scanner and was found to be approximately 59%. To improve the efficiency of curcuminoid extraction, the strach was removed from the ground turmeric using sodium chloride solution. Then the curcumanoid was extracted using aqueous solution of soap prepared by saponification of castor oil. It was found that by using 20% of soap solution (weight/volume), 88-90% of curcumanoid was exracted. The result was a brown solution, which could be easily dispersed in water.